Skrining Fitokimia dan Karakterisasi Simplisia Buah Apel Hijau (Malus sylvestris (L.) Mill) - Adinda Dewani Soetadipura; Fetri Lestari (Bandung Conference Series: Pharmacy, 2022)
Abstract. Indonesia is one of the mega biodiversity countries in the world that has high diversity, consisting of 30,000 plant species. WHO has recommended the use of traditional medicine including herbal medicine for the maintenance of public health, prevention and treatment of disease. In Indonesia, the use of medicinal plants has often been used by people from ancient times. Currently, the lifestyle of returning to nature (back to nature) is increasingly in demand by the public. According to the Basic Health Research (Riskesdas) in 2018, the percentage of Indonesians who consume traditional medicine is 38.7%. Apple is one type of fruit that is efficacious as a medicinal plant that is very popular in the community. Green apple (Malus sylvestris(L.) Mill) is a rich source of antioxidant compounds because it contains quercetin which is a flavonoid compound. Green apples have benefits for the prevention of cardiovascular disease, diabetes, inflammation, cancer, and asthma. A use of natural materials in health efforts must meet the criteria of safety, efficacy and quality. To meet these criteria, phytochemical screening and simpliciacharacterization were carried out. The results of the phytochemical screening showed that the simplicia of green apples contained a class of flavonoid compounds, polyphenols and tannins. The results of the simplicia characterization were the watersoluble extract content of 9.01 % ± 1.22; ethanol soluble extract content 22.31 % ±0.04; drying shrinkage 7.30 % ± 0.22; water content 5.5 % ± 0.7, total ash content 7 % ± 0.09; acid insoluble ash content 6.95 % ± 0.06. Abstrak. Indonesia merupakan salah satunegara mega biodiversitas di dunia yang memiliki keanekaragaman tinggi, terdiri30.000 jenis tumbuhan. WHO telahmerekomendasikan penggunaan obattradisional termasuk obat herbal untukpemeliharaan kesehatan masyarakat, pencegahan dan pengobatan penyakit. Di Indonesia sendiri pemanfaatan tumbuhanberkhasiat obat sudah sering digunakanoleh masyarakat dari jaman dahulu. Saatini, gaya hidup kembali ke alam (back to nature) semakin diminati oleh masyarakat. Menurut Riset Kesehatan Dasar (Riskesdas) tahun 2018, persentasependuduk Indonesia yang mengkonsumsiobat tradisional adalah 38,7%. Apelmerupakan salah satu jenis buah yang berkhasiat sebagai tumbuhan obat yang sudah sangat popular di masyarakat. Buahapel hijau (Malus sylvestris (L.) Mill) merupakan sumber yang kaya akansenyawa antioksidan karena mengandungquercetin yang merupakan senyawaflavonoid. Buah apel hijau memilikimanfaat sebagai pencegahan penyakitkardiovaskular, diabetes, inflamasi, kanker, dan asma. Suatu pemanfaatanbahan alam dalam upaya kesehatan harusmemenuhi kriteria keamanan, khasiat dan mutu. Untuk memenuhi kriteria tersebut, maka dilakukan skrining fitokimia dan karakterisasi simplisia. Hasil skriningfitokimia yang diperoleh menunjukkanbahwa simplisia buah apel hijaumengandung golongan senyawa flavonoid, polifenol dan tannin. Hasil darikarakterisasi simplisia yaitu kadar sari larut air 9,01 % ± 1,22; kadar sari larutetanol 22,31 % ± 0,04; susut pengeringan7,30 % ±0,22; kadar air 5,5 % ± 0,7, kadarabu total 7 % ± 0,09; kadar abu tidak larutasam 6,95 % ± 0,06.